Sex difference in the associations among hyperuricemia with self-reported peptic ulcer disease in a large Taiwanese population study - Yang, Chi-Sheng; Geng, Jiun-Hung; Wu, Pei-Yu; Huang, Jiun-Chi; Hu, Huang-Ming; Chen, Szu-Chia; Kuo, Chao-Hung (Frontiers in Medicine, 2024)
Background Hyperuricemia may play a role in various systemic diseases. However, few studies have investigated the relationship between hyperuricemia and the risk of peptic ulcer disease (PUD). Therefore, in this population-based study, we enrolled over 120,000 participants from the Taiwan Biobank (TWB) and examined the risk factors for self-reported PUD. In addition, we investigated sex differences in the association between hyperuricemia and self-reported PUD. Methods Data of 121,583 participants were obtained from the TWB. Male participants with a serum uric acid level >7 mg/dl and female participants with a serum uric acid level >6 mg/dl were classified as having hyperuricemia. Details of self-reported PUD were obtained by questionnaire. The association between hyperuricemia and self-reported PUD in the male and female participants was examined using multivariable logistic regression analysis. Results The overall prevalence of self-reported PUD was 14.6%, with a higher incidence in males (16.5%) compared to females (13.5%). After multivariable adjustment, male sex [vs. female sex; odds ratio (OR) = 1.139; 95% confidence interval (CI) = 1.084–1.198; p < 0.001], and hyperuricemia (OR = 0.919; 95% CI = 0.879–0.961; p < 0.001) were significantly associated with self-reported PUD. Further, a significant interaction was found between sex and hyperuricemia on self-reported PUD (p = 0.004). Hyperuricemia was associated with a low risk of self-reported PUD in males (OR = 0.890; 95% CI = 0.837–0.947; p < 0.001) but not in females (p = 0.139). Conclusion The prevalence of self-reported PUD was higher in the male participants than in the female participants. Hyperuricemia was associated with low prevalence of self-reported PUD in males, but not in females. Further studies are needed to clarify the mechanisms behind these observations and verify the potential protective role of hyperuricemia on the development of self-reported PUD.